PENGARUH PEMBERIAN JUS WORTEL TERHADAP PENURUNAN NYERI DYSMENORRHEA PRIMER PADA REMAJA PUTRI KELAS VII DAN VIII DI SMPN 2 MAJALENGKA TAHUN 2020 - Lia Natalia; Pipih Fitriani (Jurnal Ilmu Keperawatan dan Kebidanan, 2021)
One kind of ways to decrease the incidence of dysmenorrhea among adolescents is through  non-pharmacological method, namely by giving carrot juice. This study aims to determine the effect of carrot juice on the decrease in the level of primary dysmenorrhea among adolescent girls. This was a pre-experimental study with a one-group pretest-posttest design. The population was all students of the 7th and 8th grades of State Junior High School 2, Majalengka as many as 345 people and the samples consisted of 20 people taken with purposive sampling technique in April-June 2020. The univariate analysis was conducted using frequency distribution and the bivariate analysis was conducted using the Marginal Homogenity test. The results showed that more than half (55.0%) of adolescent girls experienced severe pain before the provision of carrot juice. Furthermore, a small proportion (10.0%) of adolescent girls experienced severe pain after the provision of carrot juice. There was an effect of carrot juice on the decrease in the level of primary dysmenorrhea among adolescent girls in the 7th and 8th grades of State Junuor High School 2, Majalengka in 2020.